Efectos jurídicos de la motivación del acto de terminación de la provisionalidad “derecho para la convivencia y la inclusión social” (2015)
The employment status of the interim in Colombia , is a topic of current concern , current and under construction , mainly by the judicial activism of the Constitutional Court , which has joined the Council of State; what not to say that the administration and Congress itself , have positions peaceful about it, because otherwise no means the approval of two ( 2) Legislative acts within three ( 3) years, whose matter was to regulate the employment of the aforementioned officials; or the issue of unification gives several judgments of the Constitutional Court. So, research has as main objective to determine the legal effects that would result in administrative and jurisdictional authority are, that is, for the administration, the public official and the judge of administrative litigation , motivation administrative through which management actions, terminated the employment of civil servants in positions of provisional career. For the purposes of work from the methodological point of view was proposed as a central methodological strategy document analysis and legal texts court; Likewise, analysis of the jurisprudence of the high courts: Council of State and the Constitutional Court, mainly on constitutional principles such as merit and motivation of administrative acts on labor, plus the study of the doctrine and comparative law on the subject mainly the Labor Administrative Law Spanish.